2023
DOI: 10.1038/s41467-023-38695-z
|View full text |Cite
|
Sign up to set email alerts
|

Cortical glutamate and GABA are related to compulsive behaviour in individuals with obsessive compulsive disorder and healthy controls

Abstract: There has been little analysis of neurochemical correlates of compulsive behaviour to illuminate its underlying neural mechanisms. We use 7-Tesla proton magnetic resonance spectroscopy (1H-MRS) to assess the balance of excitatory and inhibitory neurotransmission by measuring glutamate and GABA levels in anterior cingulate cortex (ACC) and supplementary motor area (SMA) of healthy volunteers and participants with Obsessive-Compulsive Disorder (OCD). Within the SMA, trait and clinical measures of compulsive beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…In the SMA, however, despite there being no absolute group differences in Glu, Glu/GABA levels were related to a habitual index in both patients with OCD and healthy individuals with compulsive traits. No significant group differences were found in Glu or GABA in the OCC ( 44 ). In the study presented here, we investigated how this excitatory/inhibitory balance relates to functional and dysfunctional checking within these regions.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…In the SMA, however, despite there being no absolute group differences in Glu, Glu/GABA levels were related to a habitual index in both patients with OCD and healthy individuals with compulsive traits. No significant group differences were found in Glu or GABA in the OCC ( 44 ). In the study presented here, we investigated how this excitatory/inhibitory balance relates to functional and dysfunctional checking within these regions.…”
mentioning
confidence: 77%
“…The pre-SMA and SMA are regions within the sensorimotor circuit that are known to be relevant for response inhibition and motor compulsions ( 39 ) and effective targets for brain stimulation ( 40 , 41 , 42 , 43 ). We recently found that Glu and GABA levels were significantly correlated in the 3 regions investigated in healthy volunteers but not in the OCD group, suggesting that a dysfunctional balance may contribute to the pathophysiology of OCD ( 44 ). Specifically, patients with OCD had significantly higher levels of Glu and lower levels of GABA in the ACC, resulting in significantly higher Glu/GABA ratios.…”
mentioning
confidence: 99%
“…l -Glutamic acid ( l -Glu), known as a significant excitatory amino acid neurotransmitter that influences brain functions like learning and memory in the mammalian nervous system; 1,2 serves as a nitrogen source in most mammals; 3 acts as a flavor enhancer and is commonly found in diverse foods 4 and seasonings at concentrations lower than 30 mg kg −1 ; 5 and causes certain neurological diseases such as chorea 6 and Parkinson's syndrome, 7 as well as some adverse reactions such as headache, stomach ache, and obsessive compulsive disorder, 8–10 has been found to play an indispensable role in various areas such as metabolism and control of organisms, diagnosis and treatment of diseases, and development of pharmaceutical and food industries. 11–15 Additionally, glutamate also acts as an intercellular signalling molecule 16 and moderator 17 in plants.…”
Section: Introductionmentioning
confidence: 99%
“…One important finding is the altered levels of glutamate observed in specific brain regions, such as the anterior cingulate cortex. 4 This area is critical for attention allocation and emotion regulation, and their dysregulation may contribute to OCD symptoms. The regulation of glutamate homeostasis presents a multifaceted challenge, as glutamate has the capability to diffuse beyond the confines of the synaptic cleft.…”
mentioning
confidence: 99%
“…While the stimulation of N‐methyl‐D‐aspartate (NMDA) receptors located postsynaptically facilitates the conveyance of information, synaptic plasticity, and trophic effects on neuronal cells, the triggering of NMDA receptors situated outside the synapse inhibits these functions and may precipitate excitotoxicity, resulting in neuronal damage and apoptosis. 4 , 5 Beyond glutamate levels, the transport of glutamate also appears to be affected in OCD. Glutamate transporters, which are responsible for clearing glutamate from the synaptic space to prevent excitotoxicity, may function abnormally in OCD, leading to an imbalance in excitatory signaling.…”
mentioning
confidence: 99%